( | 6 | x | − | 16 | ) | ÷ | ( | 5 | x | + | 4 | ) | = | 10 | ÷ | 9 |
Multiply both sides of the equation by: | ( | 5 | x | + | 4 | ) |
( | 6 | x | − | 16 | ) | = | 10 | ÷ | 9 | × | ( | 5 | x | + | 4 | ) |
6 | x | − | 16 | = | 10 | ÷ | 9 | × | ( | 5 | x | + | 4 | ) |
6 | x | − | 16 | = | 10 | ÷ | 9 | × | 5 | x | + | 10 | ÷ | 9 | × | 4 |
6 | x | − | 16 | = | 50 9 | x | + | 40 9 |
6 | x | − | 50 9 | x | = | 40 9 | + | 16 |
4 9 | x | = | 40 9 | + | 16 |
4 9 | x | = | 184 9 |
x | = | 184 9 | ÷ | 4 9 |
= | 184 9 | × | 9 4 |
= | 46 | × | 1 |
x | = | 46 |